2003
DOI: 10.1136/gut.52.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of E-cadherin gene in gastric mucosa associated with Helicobacter pylori infection and in gastric cancer

Abstract: Background: E-cadherin is an adhesion molecule involved in tumour invasion/metastasis. Silencing of E-cadherin by promoter CpG methylation has been shown in both familial and sporadic gastric cancers. Helicobacter pylori is a class I carcinogen in gastric cancer. Aims: This study was undertaken to investigate the association between methylation of E-cadherin and H pylori in gastric mucosa from dyspeptic patients, and in intestinal metaplasia and primary and metastatic adenocarcinoma from surgical specimens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
260
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(289 citation statements)
references
References 22 publications
23
260
2
4
Order By: Relevance
“…In this study, we investigated DNA methylation of 12 tumor-related genes, of which only 2, CDH1 and RAR-beta, have been shown to be involved in tumor invasion or metastasis. 56,57 In the present study, DNA methylation of CDH1 and RARbeta was correlated with advanced T grade. However, DNA methylation of each of the 12 genes was not associated with tumor stage but occurred frequently in the high-methylation group, and therefore, the association between high-methylation group and tumor stage is not a secondary effect of the loss of specific biologic functions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, we investigated DNA methylation of 12 tumor-related genes, of which only 2, CDH1 and RAR-beta, have been shown to be involved in tumor invasion or metastasis. 56,57 In the present study, DNA methylation of CDH1 and RARbeta was correlated with advanced T grade. However, DNA methylation of each of the 12 genes was not associated with tumor stage but occurred frequently in the high-methylation group, and therefore, the association between high-methylation group and tumor stage is not a secondary effect of the loss of specific biologic functions.…”
Section: Discussionmentioning
confidence: 84%
“…59 In GC, DNA methylation of CDH1 has been reported to be correlated with H. pylori infection. 56 Conversely, it has been reported that in nonneoplastic gastric mucosa, H. pylori infection is not correlated with the number of methylated genes. 60 In the present study, no correlation was found between methylation of any of 12 genes and presence of H. pylori infection in corresponding nonneoplastic gastric mucosa and normal gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with those of previous studies that have demonstrated the close association of HP infection with aberrant CpG island hypermethylation. [25][26][27] We found that HP infection was a confounding factor in the comparison of methylation between CG and GCN and the analysis restricted to HP-positive cases did not show any difference in the number of methylated genes between CG and GCN. This was in contrast to the previous study of Waki et al, 28 who demonstrated higher number of methylated CpG island loci in GCN than in CG using MSP.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 88%
“…Whether the methylation differences at CpGs 3, 7 and 8 contribute to TB predisposition or are merely the result of infection with M. tuberculosis and treatment of TB is unknown. Chan et al [34] showed that E-cad promoter methylation is initiated by Helicobacter pylori infection, leading to gastric carcinogenesis. Kovalenko et al [35] showed that treatment with the anti-tuberculosis drug pyrazinamide leads to methylation alterations of LINE-1 (long interspersed nucleotide elements), GSTP (glutathione-Stransferase) and p16(INK4A) genes in rat liver.…”
Section: Discussionmentioning
confidence: 99%